Avaliação do potencial biotecnológico de microorganismos da biodiversidade brasileira: biodegradação de herbicidas benzonitrilados - Oliveira, Karina Ota [UNESP] (2015)
Biocatalysis is the use of enzymes (microbial, plant or animal) to catalyze chemical transformations, primarily of organic compounds. Generally, enzymatic reactions are much more attractive than the classical chemical alternatives, as they use catalysts that are potentially chemo-, region- and stereoselective, biodegradable, which come from renewable sources and that require mild reaction conditions in terms of pH, temperature and pressure and the use of environmentally friendly solvents (water, supercritical fluids, ionic liquids). Therefore and associated to the socioeconomic and environmental pressures exerted on industries to use sustainable and more efficient processes, the search for new biocatalysts has increased considerably. Nitriles converting enzymes are among the most widely ones used industrially. In addition to their synthetic value, these enzymes play a key role in protecting the environmental as they have been successfully used in the biodegradation and bioremediation of areas contaminated by man-made organic nitriles. Thus, herein we intend to investigate microorganisms from Brazilian biodiversity in terms of enzymes involved in the metabolism of nitriles, more specifically nitrilases (Nase), nitrile hydratase (NHase), amidases and hydroxynitrile lyase (HNLase) through colorimetric assays. It was found 1 positive hit for nitrile hydratase/amidase, 8 for nitrilases and 3 microorganisms with undefined enzymatic system within the 29 evaluated microorganisms. Regarding the enzyme hydroxinitrile lyase, 76 microorganisms were evaluated and 27 positive hits were found. Those colorimetric assays were confirmed through chromatographic and spectrometrically techniques. The positive hits found in the colorimetric assay were applied in the study of biodegradation of Totril® herbicide. These reactions were monitored by HPLC-MS/MS and there were found 5 biodegradation products...